Sustainable Cross-Laminated Timber Structures in a Seismic Area: Overview and Future Trends - Antonio Sandoli; Claudio D’Ambra; Carla Ceraldi; Bruno Calderoni; Andrea Prota (Applied Sciences, 2021)
Cross-laminated timber (CLT) buildings are recognized as a robust alternative to heavyweight constructions, because beneficial for seismic resistance and environmental sustainability, more than other construction materials. The lightness of material and the satisfactory dissipative response of the mechanical connections provide an excellent seismic response to multi-story CLT buildings, in spite of permanent damage to timber panels in the connection zones. Basically, CLT constructions are highly sustainable structures from extraction of raw material, to manufacturing process, up to usage, disposal and recycling. With respect to other constructions, the potential of CLT buildings is that their environmental sustainability in the phases of disposal and/or recycling can be further enhanced if the seismic damage in structural timber components is reduced or nullified. This paper reports a state-of-the art overview on seismic performance and sustainability aspects of CLT buildings in seismic prone regions. Technological issues and modelling approaches for traditional CLT buildings currently proposed in literature are discussed, focusing the attention on some research advancements and future trends devoted to enhance seismic performance and environmental sustainability of CLT buildings in seismic prone regions.